G1 Cell Cycle Arrest Is Induced by the Fourth Extracellular Loop of Meningococcal PorA in Epithelial and Endothelial Cells - Matthew Vassey; Rininta Firdaus; Akhmed Aslam; Lee M. Wheldon; Neil J. Oldfield; Dlawer A. A. Ala’Aldeen; Karl G. Wooldridge (Cellular Microbiology)
Neisseria meningitidis is the most frequent cause of bacterial meningitis and is one of the few bacterial pathogens that can breach the blood-brain barrier (BBB). The 37/67 kDa laminin receptor (LamR) was previously identified as a receptor mediating meningococcal binding to rodent and human brain microvascular endothelial cells, which form part of the BBB. The meningococcal surface proteins PorA and PilQ were identified as ligands for this receptor. Subsequently, the fourth extracellular loop of PorA (PorA-Loop4) was identified as the LamR-binding moiety. Here, we show that PorA-Loop4 targets the 37 kDa laminin receptor precursor (37LRP) on the cell surface by demonstrating that deletion of this loop abrogates the recruitment of 37LRP under meningococcal colonies. Using a circularized peptide corresponding to PorA-Loop4, as well as defined meningococcal mutants, we demonstrate that host cell interaction with PorA-Loop4 results in perturbation of p-CDK4 and Cyclin D1. These changes in cell cycle control proteins are coincident with cellular responses including inhibition of cell migration and a G1 cell cycle arrest. Modulation of the cell cycle of host cells is likely to contribute to the pathogenesis of meningococcal disease.